Oxidant and antioxidant mechanisms in chronic kidney disease (Annals of Medical Research, 2021)
None
Keywords: Chronic Kidney Disease; Platelet-Activating Factor-Acetylhydrolase; Paraoxonase-1; Malondialdehyde.